REALIZING FAIR BUSINESS COMPETITION IN THE INDONESIAN BUSINESS WORLD IN THE ERA OF GLOBALIZATION - Suparnyo (International Journal of Psychosocial Rehabilitation, 2020)
The development of the global economy shows symptoms of unfair economic competition, especially the presence of monopoly efforts of the world economic power. This kind of phenomenon will certainly affect economic conditions including economic growth which will only be influenced by large corporations from super power countries. In Indonesia itself, there are indications of efforts to monopolize business by large corporations that will unconsciously erode the national economy at the macro level and the economy of small people. Hence, the problem lies on the way Indonesia prepares itself to overcome these things, especially in the development of the legal system that regulates the formal legal business competition. This article aims to describe the way the legal position and system in Indonesia should be formed to overcome the negative impacts of business competition and create fair business competition. The utilized method was the socio legal research approach which is intended to study and examine the interrelationship between the law with other institutions.